Edukasi Kesehatan Waspada Terhadap Kolesterol dan Tekanan Darah Tinggi Sebagai Ancaman Tersembunyi bagi Pendengaran - Eka Arie Yuliyani; Ika Parasetyaningrum; Athalita Andhera Nabil (Universitas Mataram, 2026)
High cholesterol and hypertension are major cardiovascular risk factors that can negatively affect hearing function through vascular disturbances in the inner ear. However, public awareness regarding the relationship between metabolic disorders and hearing impairment remains limited. This community service activity aimed to increase public knowledge and awareness of the potential impact of high cholesterol and hypertension on hearing health. The health education program was conducted on September 30, 2025, at the ENT Outpatient Clinic of West Nusa Tenggara Provincial Hospital and targeted patients and their companions from various age groups. The activity was organized collaboratively by medical students from the Faculty of Medicine and Health Sciences, University of Mataram, under the supervision of an otolaryngologist and in cooperation with the hospital’s Health Promotion Team. Educational materials were delivered through interactive presentations supported by visual aids and followed by quizzes and discussion sessions. The implementation of the program was carried out in an interactive and conducive atmosphere, with participants actively engaging in discussions and responding enthusiastically to the educational content. The activity provided participants with a better understanding of the association between hypertension, hypercholesterolemia, and hearing disorders, as well as preventive measures that can be undertaken to maintain both hearing and cardiovascular health. This educational program is expected to encourage early detection, healthy lifestyle practices, and better management of metabolic risk factors to prevent hearing impairment and improve overall quality of life